2004
DOI: 10.2139/ssrn.650542
|View full text |Cite
|
Sign up to set email alerts
|

Modelling Water Trade in the Southern Murray-Darling Basin

Abstract: Introduction 1 2 Water trade and irrigation in the southern Murray-Darling Basin 3 Irrigation water sources and irrigation districts 3 Water entitlements and seasonal allocations 5 Utility charges 6 Quantities of water traded 8 Water trade prices 9 Constraints on water trading 11 3 Overview of the modelling approach 19 Development of a water module within TERM 20 Incorporating water trade 23 Model simulation 27 4 Long run effects of reduced water availability with trade 29 Macroeconomic effects of water trade … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 8 publications
(5 reference statements)
1
35
1
Order By: Relevance
“…Most trade occurs in seasonal allocations, and it is common for 10 -20 per cent of allocations to be traded within an irrigation district in an irrigation season (Peterson et al 2004). Although trade in allocations has increased over recent years, trade in water entitlements remains small, at less than 1 per cent of diversions in [2001][2002].…”
Section: Trade In Water Entitlements and Allocationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most trade occurs in seasonal allocations, and it is common for 10 -20 per cent of allocations to be traded within an irrigation district in an irrigation season (Peterson et al 2004). Although trade in allocations has increased over recent years, trade in water entitlements remains small, at less than 1 per cent of diversions in [2001][2002].…”
Section: Trade In Water Entitlements and Allocationsmentioning
confidence: 99%
“…Although water may become more mobile as these investments reach the end of their economic life, the demand for water for environmental purposes is likely to be an important driver of future trading patterns. Peterson et al (2004) used a computable general equilibrium model to estimate the regional impacts of expanding trade in the southern Murray-Darling Basin under a number of scenarios where water availability was reduced by 10, 20, and 30 per cent. With a 10 per cent reduction in water availability, total net water trade in the southern Murray-Darling Basin was found to be a relatively small proportion of total allocations, with only 2.3 per cent of allocations traded among regions.…”
Section: Implicit Water Rights and Tradementioning
confidence: 99%
“…It could also provide greater flexibility for rural users to react to changing circumstances, such as changes in climatic conditions and water availability. Peterson et al (2004) examined the likely economic effects of expanding water trade among irrigators in the southern Murray-Darling Basin (MDB) using a computable general equilibrium (CGE) model, TERM-Water, developed by the Centre of Policy Studies at Monash University. This study found that allowing both intra-and interregional water trade among irrigators substantially lessens the impact of reducing water availability on gross regional product.…”
Section: Introductionmentioning
confidence: 99%
“…Dwyer et al (2005) The gains from water trade between irrigators in Victoria were simulated in research by Peterson et al (2004). The simulation results indicated that, "water entitlements, … were significantly more expensive than temporary trades (Productivity Commission 2005; Peterson et al 2004).…”
Section: Other Australian Iwrm Examplesmentioning
confidence: 99%
“…The simulation results indicated that, "water entitlements, … were significantly more expensive than temporary trades (Productivity Commission 2005; Peterson et al 2004). Further this water trade had the potential to reduce the effects of water scarcity on gross regional product (Peterson et al 2004). …”
Section: Other Australian Iwrm Examplesmentioning
confidence: 99%